Towards a refined architecture for socio-technical decentralized identity services - Hwang, Hwajeong; Park, Minjung; Oh, Hyunyoung; Chai, Sangmi (Frontiers in Blockchain, 2025)
The accelerating adoption of artificial intelligence, together with escalating incidents of identity theft, account hacking, and large-scale personal data breaches, is driving a global shift toward secure, user-centric identity management systems. Blockchain-based Decentralized Identity (DID) services, grounded in the principles of Self-Sovereign Identity (SSI), are increasingly recognized as a foundational technology for safeguarding personal data and enabling user-controlled identity management. However, existing DID research and implementations remain predominantly technology-focused, often overlooking socio-technical factors such as governance, usability, operational effectiveness, and stakeholder trust. To address this gap, this study proposes an STS-based (Socio-Technical Systems) framework to guide the practical and scalable adoption of DID services, integrating both social components (e.g., governance, sustainability, user-centric design) and technical components (e.g., decentralization, privacy preservation, interoperability, security). Using an integrative research review methodology, the framework was developed through systematic analysis of global standards, industry cases, and academic literature, and was further refined and validated through multidisciplinary expert consultation. Building on this framework, we introduce a Refined DID Service Architecture optimized for enterprise-level deployment, incorporating privacy-preserving mechanisms at the infrastructure level, consensus-based governance, and standardized UI/UX guidelines. The proposed architecture addresses key barriers to adoption--such as interoperability gaps, regulatory inconsistencies, and limited user engagement--while ensuring scalability and compliance with global standards. This study contributes to both theory and practice by (1) framing DID as a socio-technical system, (2) providing an actionable evaluation framework for developers, regulators, and service providers, and (3) offering a globally adaptable architecture that balances technological robustness with social acceptance, thereby supporting the broader diffusion of DID services in real-world ecosystems.